Highly sensitive nano-sensor based on a binary photonic crystal for the detection of mycobacterium tuberculosis bacteria - Taya, Sofyan A.; Daher, Malek G.; Colak, Ilhami; Ramahi, Omar M. (Journal of materials science. Materials in electronics, 2021)
Tuberculosis is a widespread disease all over the world. Early diagnosis plays a crucial role in the treatment of patients and can reduce the mortality rate. A new biosensor based on a binary photonic crystal is designed for the detection of mycobacterium tuberculosis bacteria in the blood. The structure air/(A/B) N /(Defect)/(A/B) N /air is employed, where A, B and N are the first and second layers and the number of periods, respectively. Layers A and B are chosen as GaAs and BaF 2 , respectively. The defect layer is the blood sample. The transfer matrix method (TMM) is utilized to simulate the structure. Some parameters, such as central wavelength, defect layer thickness and incident angle are optimized to maximize the sensitivity. The optimum sensitivity is found 3197.18 nm/RIU, which is extremely high when compared to the most recent papers published in this field. In addition, our sensor has a simple design, tunable fabrication and low cost and can be useful for the detection of many organisms that can exist in the blood.